Penguatan kemampuan guru dalam pengembangan media pembelajaran menggunakan virtual reality - Muliaty Muliaty; Suhartono Suhartono (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
his activity aims to design and develop an application as learning media to help teachers in visualizing abstract learning materials easier to be understood, to increase students' interest and motivation in learning process, and to develop interesting learning media. Method used are discussion, lecturing, demonstration, simulation, and evaluation. The discussion method is used to know the general knowledge of the participants on multimedia applications and supporting technology. Lecturing method is used in delivering theories on software and hardware as well as maintenance. Demonstration is used to show the steps in making game application. Simulation method is used to show the virtual reality and its effectiveness of the implemented application. Evaluation method is used to audit or evaluate participants’understanding on technology, 3D unity application and the result of the multimedia by operating, limited feedback, interaction, realistic graphic, graphic display, transfer and manipulation, distribution between objects between virtual environments, environmental features, interactions with other controls and other hard fixing problems. The result shows that majority of the participants understand the supporting technology, able to design, create, and implement virtual reality. The use of virtual reality technology can be used as an intermediary to facilitate the delivery of material, and as learning medium that can improve the effectiveness of student learning. Furthermore, in order to guard the follow-up to the perpetuation process, the team guided the participants in making virtual reality.